Social Inequality on Women in Khaled Hosseini’s “A Thousand Splendid Suns” Novel - Fitria Deviana; Danu Wahyono (Austronesian: Journal of Language Science & Literature, 2024)
The research aims to explain the causes of social inequality on women, the effects of social inequality on women, and the types of social inequality on women in Khaled Hosseini’s A Thousand Splendid Suns. The analysis uses literary theory sociology. The primary data used is a novel, A Thousand Splendid Suns. This research uses qualitative descriptive research. Descriptive research involves collecting novels and answering questions about the complications consistent with the problem statement. As a result, internal causes that occur in A Thousand Splendid Suns are low education and gender inequality. The external cause is due to the patriarchal system. Then, the positive effect of social inequality on Mariam is that she can be patient and tough. At the same time, the negative effect is that she often gets violence and oppression. Laila’s positive effect is that she becomes a brave woman who does not give up easily. The negative effect is that Laila often experiences violence and oppression. The social type of inequality in A Thousand Splendid Suns is the Existential type, meaning the unequal recognition of the human individual as a person. The findings from this analysis can help us understand more about the patriarchal system and make Laila a woman who is even more courageous in voicing rights related to gender equality, especially women’s rights.